2001
DOI: 10.4314/wsa.v27i3.4978
|View full text |Cite
|
Sign up to set email alerts
|

A generalised solution for step-drawdown tests including flow dimension and elasticity

Abstract: Step-drawdown and multi-rate tests present convenient tools for the estimation of the long-term yield of boreholes. However, the analytical methods commonly employed for the analysis of such tests are all based on the assumption that the drawdown in a borehole is a linear function of the discharge rate. Numerous constant rate tests, of which a few are discussed in this paper, has shown that this is not necessarily the case with boreholes drilled in the Karoo formations of South Africa. The drawdowns in these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…A recharge rate of 15 mm/year. and a pumping period of 1 year were applied, producing a sustainable yield of 0.41 L/s (or as later changed to 0.48 L/s by van Tonder et al 2001b). The result was similar to the 0.36 L/s estimated by their FC-method; except, in that case, the pumping period was assumed to be 2 years.…”
Section: Analytical Techniquessupporting
confidence: 61%
See 1 more Smart Citation
“…A recharge rate of 15 mm/year. and a pumping period of 1 year were applied, producing a sustainable yield of 0.41 L/s (or as later changed to 0.48 L/s by van Tonder et al 2001b). The result was similar to the 0.36 L/s estimated by their FC-method; except, in that case, the pumping period was assumed to be 2 years.…”
Section: Analytical Techniquessupporting
confidence: 61%
“…Using data from a test of well UO5 at an extensively monitored research test site, they conducted a numerical analysis to verify their model, where the available drawdown was related to the depth of a single, discrete horizontal fracture. Van Tonder et al (2001b) proposed that natural fractures may close over time, due to deformation of an aquifer as water levels in a well decline. Although these were comprehensive studies, no operational data were presented to confirm the researchers' estimates of long-term well yields.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the modification of Rorabaugh [1953] to account for unknown c is frequently invoked. Additionally, it is often found necessary to treat B as a function of time [ Helweg , 1994; van Tonder et al , 2001] leading to complicated overparameterized empirical functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mathias et al [2008] showed that for large times, the drawdown response of a well‐being pumped at a constant rate, according to the Forchheimer equation, can be approximated by Mathias et al [2008] were only interested in Forchheimer flow to wells for constant abstraction rates and therefore did not consider SDTs or Jacob's method. However, comparison of and would suggest that (when c = 2) is a large time approximation for Forchheimer flow to a well with a piecewise constant abstraction rate, whereby Jacob's well‐loss coefficient, B , is related to the Forchheimer parameter by In this paper, following the work of Helweg [1994] and van Tonder et al [2001], it is proposed that the main shortcoming of the Jacob method is due to the assumption of a constant B coefficient. The assumption of constant B is equivalent to approximating only the large time behavior of the Forchheimer equation.…”
Section: Introductionmentioning
confidence: 99%
“…The stepwise mode of drawdown is common in the TMG sandstones and many other fractured rock aquifers in South Africa (Van Tonder et al, 2001), and is often explained as being set off by multiple boundary effects. This is true if only one flow system is intercepted by a borehole.…”
Section: Fracture Connectivity Patternmentioning
confidence: 99%